Mycobacterium - Research and Development 2018
DOI: 10.5772/intechopen.73542
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Non Tuberculosis Mycobacterial Lung Diseases

Abstract: Nontuberculosis mycobacteria (NTM) are ubiquitous in nature and opportunistically infect different animals, including humans. Currently, NTM is emerging as an important cause of pulmonary infection among both immunocompromised and immunocompetent persons worldwide. The clinical relevance of pulmonary NTM varies among species while showing geographical heterogeneity in distribution as well as pathogenicity. The outcome of the respiratory NTM disease is a consequence of a complex interplay between microbial fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 133 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…Also, sputum smear microscopy does not distinguish NTM from M. tuberculosis, as bacilli in both cases are acid-fast and morphologically similar in appearance. Adhikaram found that patients with NTM-PD have been erroneously diagnosed as having tuberculosis and multidrug-resistant tuberculosis in 4.5 to 15% and 18 to 20% cases, respectively [2]. Guidelines for detecting NTM-PD were established in 2007 by the American Thoracic Society and the Infectious Diseases Society of America [3].…”
Section: Introductionmentioning
confidence: 99%
“…Also, sputum smear microscopy does not distinguish NTM from M. tuberculosis, as bacilli in both cases are acid-fast and morphologically similar in appearance. Adhikaram found that patients with NTM-PD have been erroneously diagnosed as having tuberculosis and multidrug-resistant tuberculosis in 4.5 to 15% and 18 to 20% cases, respectively [2]. Guidelines for detecting NTM-PD were established in 2007 by the American Thoracic Society and the Infectious Diseases Society of America [3].…”
Section: Introductionmentioning
confidence: 99%